Selective nanofibers patterning via electric field-enhanced electrospinning - Ding, Zhenweng; Wan Salim, Wan Wardatul Amani; Ziaie, Babak (ACS Publications, 2009)
In this paper, we demonstrate a nanofiber patterning technique using field-enhanced electrospinning. Polyethylene oxide (PEO) nanofibers were electrospun on an elastomeric substrate with gold-coated pyramidal protrusions with the majority of fibers being deposited at the tips. The deposited nanofiber spots ranged from 8 × 8 μm2 to 60 × 60 μm2 in size, uniformly covering an area of 5 × 10 mm2. Our experiments also indicate that nanofiber pattern selectivity is highly dependent on the separation/size ratio of the pyramidal protrusions with a ratio of <1, resulting in a superior selectivity.